The Assessment of the Quality of Existing Parks along Phewa Lake, Pokhara, Nepal - Thapa, Luna; Kandel, Samikshya (Technical Journal, 2023)
This paper aims to identify the quality criteria to assess the quality of parks and examines the quality of urban parks along Phewa Lake in Lakeside, Pokhara. After a comprehensive study of relevant literature, six criteria are selected for the quality assessment of the urban parks under study; Accessibility, Distinctive Characteristics, Activities, Condition of landscape elements, Condition of utilities and services, and Cleanliness. The criteria are further divided into sub-criteria for the study. Field visits, observation, and key informants’ interviews were conducted to collect data and triangulate results. The findings revealed the existing quality of the urban parks in terms of the selected criteria of assessment. The quality condition of a park differs from one criterion to another and also differs from one park to another. The results from the study will be beneficial in improving the quality of the parks by focusing on the criteria where the park is lagging.